How does social media drive corporate carbon disclosure? Evidence from China - Shao, Jing; He, Zhiwei (Frontiers in Ecology and Evolution, 2022)
As public concern over global warming increases, there is a growing requirement for companies, as carbon emitters, to disclose (and work to reduce) their carbon emissions. Previous literature has neglected the role of social media as a source of legitimacy pressure to influence corporate carbon disclosure. Based on legitimacy theory, this study analyzed the impact of social media legitimacy pressure on corporate carbon disclosure using data from 3656 Chinese listed companies from 2009 to 2019. We found that social media legitimacy pressure significantly enhances corporate carbon disclosure. Additionally, this positive relationship is weakened by substantive corporate internal carbon management measures (corporate green innovation and environmental management systems). Accordingly, in order to ensure consistent carbon management practices, companies should focus their efforts on substantive carbon management measures along with carbon disclosure.